PENGARUH DINING EXPERIENCE TERHADAP KEPUASAN KONSUMEN DAN REVISIT INTENTION DI RESTORAN INDONESIA DI KOREA SELATAN (STUDI KASUS DI BALI RESTO , DAEJEON) - Ista Salsabila; Rosie Oktavia Puspita Rini (Media Bina Ilmiah, 2023)
This research was conducted to analyze and determine the effect of dining experience on customer satisfaction and visit intention at Indonesian restaurants in the Daejeon area, South Korea. The dimensions of the dining experience used in this study are food quality, service quality and physical environment. This research used a sampling method involving 96 respondents who had eaten at the Bali Resto restaurant in South Korea. Data analysis using Smart PLS (Partial Least Square). The results showed that food quality and service quality had an effect on consumer satisfaction but not on revisit intention. Physical environment has a significant impact on revisit intention, but not on customer satisfaction. In addition, customer satisfaction also has a significant impact on revisit intentions.